2022
DOI: 10.3389/fpsyg.2022.970362
|View full text |Cite
|
Sign up to set email alerts
|

Integrating positive psychology and spirituality in the context of climate change

Abstract: In the context of climate change and its accompanying impact on stress and mental health, we argue that positive psychology (PP) may benefit from an integration of spirituality to better support people’s wellbeing. Starting with an overview of climate change’s impact on wellbeing and health, we explore the paradoxical and complex relationship between humans and nature. Following which, we will briefly define spirituality and present an evocative metaphor of the wave to portray the evolution of the field of PP.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Appendix 1 outlines the results of the MMAT quality appraisal of the individual studies. One study was identified as a mixed method (Nawrath et al, 2022 ), nine as qualitative studies (Bellehumeur et al, 2022 ; Lestar & Böhm, 2020 ; Cloud & Redvers, 2023 ; Denis et al, 2022 ; Hategan, 2021 ; Keaulana et al, 2021 ; Skoko et al, 2021 ; Nalau et al, 2018 ; Oberholzer-Dent et al, 2023 ), and four as quantitative studies (Kras & Keenan, 2020 ; Oliveira et al, 2022 ; Vitorino et al, 2018 ; Walls et al, 2022 ). All included studies addressed both screening questions, stated the research aims, and justified the findings to answer the research questions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations

Ecospirituality and Health: A Systematic Review

de Diego‑Cordero,
Martínez-Herrera,
Coheña-Jiménez
et al. 2024
J Relig Health
“…Appendix 1 outlines the results of the MMAT quality appraisal of the individual studies. One study was identified as a mixed method (Nawrath et al, 2022 ), nine as qualitative studies (Bellehumeur et al, 2022 ; Lestar & Böhm, 2020 ; Cloud & Redvers, 2023 ; Denis et al, 2022 ; Hategan, 2021 ; Keaulana et al, 2021 ; Skoko et al, 2021 ; Nalau et al, 2018 ; Oberholzer-Dent et al, 2023 ), and four as quantitative studies (Kras & Keenan, 2020 ; Oliveira et al, 2022 ; Vitorino et al, 2018 ; Walls et al, 2022 ). All included studies addressed both screening questions, stated the research aims, and justified the findings to answer the research questions.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies indicate that exposure to natural disasters or knowledge about them generates significant stress or anxiety in some individuals. This situation can generate frustration and helplessness owing to the inevitable consequences of the environmental crisis, both in the short and long term (Bellehumeur et al, 2022 ). Similarly, other studies have explained how the natural environment prevents or helps against certain mental disorders such as depression, anxiety, and substance abuse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations

Ecospirituality and Health: A Systematic Review

de Diego‑Cordero,
Martínez-Herrera,
Coheña-Jiménez
et al. 2024
J Relig Health
“…At the same time, there is a possibility of ignoring some meaningful literature. For example, in considering the role of positive psychology in global issues, some researchers suggest that positive psychology may benefit from the integration of spirituality to better support people's well-being (Bellehumeur et al, 2022); others have found that positive psychology has a considerable impact on employees' green behavior (Meyers and Rutjens, 2022). Second, we did not conduct an in-depth assessment of the literature, only those in WoSCC; other databases, such as Scopus, MEDLINE, and PubMed, are available.…”
Section: Strengths and Limitationsmentioning
confidence: 99%